FENOMENA CADAR DALAM PROSES HIJRAH (Analisa Hukum dan Presepsi Masyarakat Pengguna Cadar) - Ace Somantri (Bayani, 2021)
The issue of radicalism and fundamentalism is still in the news aimed at Muslims. The phenomenon of hijrah has become a trend among the Muslim community, Anis Baswedan responded positively as an indication of the awakening of Islam, but there are differences of opinion, according to Ahmad Muzaki that the phenomenon of hijrah must have assistance in order to avoid entering the door of their version of terrorism. One of the phenomena of hijrah is that many Muslim women use the veil / niqob. The formulation of the problem that is used as the limitation of this study is more focused on understanding Islamic law and perceptions of the use of the veil / niqob among the hijrah community. The research method used is through a descriptive qualitative approach. The results showed that there was a diversity of opinions regarding the use of the niqab / veil, giving rise to a diversity of beliefs about the perfection of Muslims (for Muslim women) in believing by using the niqab / veil. Muslim communities who are in the process of hijrah believe that faith is an absolute necessity and must be present in every Muslim. As a consequence of this faith, Muslims are obliged to carry out the stipulated syari'at, including in terms of dress.